Never too old to get rich : the entrepreneur's guide to starting a business mid-life - Hannon, Kerry (John Wiley & Sons, Inc., 2019)
Start a successful business mid-life When you think of someone launching a start-up, the image of a twenty-something techie probably springs to mind. However, Gen Xers and Baby Boomers are just as likely to start businesses and reinvent themselves later in life. Never Too Old to Get Rich is an exciting roadmap for anyone age 50+ looking to be their own boss and launch their dream business. This book provides up-to-date resources and guidance for launching a business when you're 50+. There are snappy profiles of more than a dozen successful older entrepreneurs, describing their inspirational journeys launching businesses and nonprofits, followed by Q & A conversations, and pull-out boxes containing action steps. The author walks you through her three-part fitness program: guidelines for becoming financially fit, physically fit, and spiritually fit, before delving more deeply into how would-be entrepreneurs over 50 can succeed." Describes how you can find capital to start your own business " Offers encouraging stories of real people who have become their own bosses and succeeded as entrepreneurs " Written by PBS Next Avenue's entrepreneur expert, Kerry Hannon " Teaches you how to start your own business Never Too Old to Get Rich is the ideal book for older readers looking to pursue new business ventures later in life